Oxidant stress in Neisseria gonorrhoeae: adaptation and effects on L-(+)-lactate dehydrogenase activity. - Fu, H S (1989)
Neisseria gonorrhoeae, an obligate human pathogen, is subjected to oxidant stress when attacked by O2 reduction products formed by neutrophils. In this study, exposure of gonococci to sublethal concentrations of superoxide and hydrogen peroxide (and related O-centered radicals) resulted in phenotypic resistance to oxidant stress. Adaptation required new protein formation but was not related to increases in superoxide dismutase or catalase. We have previously demonstrated that gonococci use phagocyte-derived L-(+)-lactate. Oxidant stress of greater magnitude than that required for adaptation led to a generalized increase in bacterial metabolism, particularly in L-(+)- and D-(-)-lactate utilization and lactate dehydrogenase activity. Increased lactate utilization required new protein synthesis. These results suggest the possibility that lactate metabolism is of importance to N. gonorrhoeae subjected to oxidant stress. Use of lct mutant organisms unable to use L-(+)-lactate should allow examination of this hypothesis.